Assessment of Creative Movement in Preschool Children - Gorshkova E.V (Moscow State University of Psychology and Education, 2020)
The paper presents a technique for assessing features of creative movement in children aged 3-6 years; the technique was used to test the hypothesis about the specifics of these features in each of the preschool ages. The paper outlines the creative task and the entire procedure of the technique; describes the parameters of creative movement (the use of various expressive movements, their originality, transformation into the character etc.) and the system of their assessments. The study involved 205 children aged 3-6 and the paper discusses the obtained data: compares the developmental dynamics of creative movement basing on its parameters and the correlation between them; provides intermediate conclusions concerning the predominance of the cognitive aspect of creativity ("use of means" of the language of movements) over the actual creative aspect ("transformation into the character", "originality").